Pengembangan Materi dan Bahan Ajar PAI Dengan Model Dick And Carey - Erika Fauziah; Ucik Saidatur Rohmah (Social Science Academic, 2024)
The Dick and Carey’s model is a learning model that has procedures with an instructional design consisting of systematic steps, consisting of cognitive and behavioral elements that require student responses to the material presented. So that this learning model is suitable with PAI materials and teaching materials, and can include knowledge, attitudes and skills, which are learning-oriented.